Web Usage Data as a Means of Evaluating Public Health Messaging and Outreach - Tian, Hao; Brimmer, Dana J; Lin, Jin-Mann S; Tumpey, Abbigail J; Reeves, William C (JMIR Publications, 2009)
Background The Internet is increasingly utilized by researchers, health care providers, and the public to seek medical information. The Internet also provides a powerful tool for public health messaging. Understanding the needs of the intended audience and how they use websites is critical for website developers to provide better services to the intended users. Objective The aim of the study was to examine the utilization of the chronic fatigue syndrome (CFS) website at the Centers for Disease Control and Prevention (CDC). We evaluated (1) CFS website utilization, (2) outcomes of a CDC CFS public awareness campaign, and (3) user behavior related to public awareness campaign materials and CFS continuing medical education courses. Methods To describe and evaluate Web utilization, we collected Web usage data over an 18-month period and extracted page views, visits, referring domains, and geographic locations. We used page views as the primary measure for the CFS awareness outreach effort. We utilized market basket analysis and Markov chain model techniques to describe user behavior related to utilization of campaign materials and continuing medical education courses. Results The CDC CFS website received 3,647,736 views from more than 50 countries over the 18-month period and was the 33rd most popular CDC website. States with formal CFS programs had higher visiting density, such as Washington, DC; Georgia; and New Jersey. Most visits (71%) were from Web search engines, with 16% from non-search-engine sites and 12% from visitors who had bookmarked the site. The public awareness campaign was associated with a sharp increase and subsequent quick drop in Web traffic. Following the campaign, user interest shifted from information targeting consumer basic knowledge to information for health care professionals. The market basket analysis showed that visitors preferred the 60-second radio clip public service announcement over the 30-second one. Markov chain model results revealed that most visitors took the online continuing education courses in sequential order and were less likely to drop out after they reached the Introduction pages of the courses. Conclusions The utilization of the CFS website reflects a high level of interest in the illness by visitors to the site. The high utilization shows the website to be an important online resource for people seeking basic information about CFS and for those looking for professional health care and research information. Public health programs should consider analytic methods to further public health by understanding the characteristics of those seeking information and by evaluating the outcomes of public health campaigns. The website was an effective means to provide health information about CFS and serves as an important public health tool for community outreach.